(untitled) (REMUNOM, 2025)
The increased use of concrete in construction is increasing the demand for Portland cement, whose production accounts for approximately 8% of global CO2 emissions. This study was motivated by the need for alternatives to Portland cement, thus leading to the emergence of ternary cement, but with the need to evaluate its life cycle. This study aimed to investigate the environmental impact, in terms of CO2-eq emissions, of the production of ternary cements formulated with blast furnace slag (EGA) and fly ash (CV), the results of which were also compared to conventional Portland cement. This study used data from experiments conducted in the laboratories of the Federal University of Pará (UFPA), relating to the production of ternary cement from the combination of BFS with BFS and Portland cement. To this end, two ternary cement formulations (CT1 and CT2) with different clinker replacement ratios were analyzed, respecting the limits of NBR 16697. The results showed that CT1 emitted 297.55 kg of CO2-eq, while CT2 emitted 217.04 kg of CO2-eq, compared to 865 kg of CO2-eq for traditional Portland cement. The production and transportation of Portland cement accounted for up to 87.21% of the total emissions in ternary cements, confirming that clinkerization is the main impact factor. It is concluded that ternary cements, especially those with lower clinker content, have environmentally favorable potential without compromising regulatory requirements.